How Learners’ Corrective Feedback Beliefs Modulate Their Oral Accuracy: A Comparative Study on High- and Low-Accuracy Learners of Chinese as a Second Language - Zhang, Jingwei; Cao, Xianwen; Zheng, Nan (Frontiers in Psychology, 2022)
This paper explores the differences in high-accuracy and low-accuracy learners’ beliefs about corrective feedback in the Chinese as a second language (henceforth, CSL) classroom. In this study, we collected data through a questionnaire survey and an oral test with 76 CSL learners in a Chinese university. The analysis revealed that both high- and low-accuracy CSL learners shared the same beliefs in whether and how the learner errors should be corrected but differed in their beliefs about when is the best time to correct, which error should be corrected, and who the corrector should be. Specifically, the discrepancy between high- and low-accuracy groups’ beliefs about corrective feedback was found to be related to the participants’ oral accuracy. The same corrective feedback beliefs held by high-accuracy groups have implications for improving low-accuracy groups’ oral accuracy. Through comparison with findings on corrective feedback beliefs of English as a foreign/second language (henceforth, EFL/ESL) learners, this study indicated CSL learners’ corrective feedback beliefs and suggested that language pedagogies need to be developed from the perspective of language learners’ corrective feedback beliefs.